Website-Based E-Market (E-Patali) Application For Gorontalo City Central Market - Sulistiawati Rahayu Ahmad (Universitas Negeri Padang, 2023)
The rapid growth of technology has an impact on the world of marketing, marketing trends are switching from offline to online. The level of consumption of Gorontalo people continues to increase, but the market will only look crowded on any given day or ahead of the religious big day. The current condition, the quiet interest of prospective buyers due to the easy access of technology in online shopping should be used as an opportunity to increase sales of market traders. In addition to selling conventional merchandise can also sell online. The purpose of this research is to produce a website-based e-market application that allows traders in the central market to sell online and increase revenue and reduce operational costs. An e-commerce app called E-market. This e-market itself is not the first time because already e-markets that work with BRI that can be accessed https://e-pasar.bri.co.id/ but after being searched deeper into the website the Central market is not included in the digital market. The results of this study were later implemented in Gorontalo Central Market traders to increase their sales through online transactions, by not leaving the old sales system (Offline).